A Novel Mutation in ERCC8 Gene Causing Cockayne Syndrome - Taghdiri, Maryam; Dastsooz, Hassan; Fardaei, Majid; Mohammadi, Sanaz; Farazi Fard, Mohammad Ali; Faghihi, Mohammad Ali (Frontiers in Pediatrics, 2017)
Cockayne syndrome (CS) is a rare autosomal recessive multisystem disorder characterized by impaired neurological and sensory functions, cachectic dwarfism, microcephaly and photosensitivity. This syndrome shows a variable age of onset and rate of progression and its phenotypic spectrum include a wide range of severity. Due to the progressive nature of this disorder, diagnosis can be more important when additional signs and symptoms appear gradually and become steadily worse over time. Therefore, mutation analysis of genes involved in CS pathogenesis can be helpful to confirm the suspected clinical diagnosis. Here, we report a novel mutation in ERCC8 gene in a 16-year-old boy who suffers from poor weight gain, short stature, microcephaly, intellectual disability and photosensitivity. The patient was born to consanguineous family with no previous documented disease in his parents. To identify disease causing mutation in the patient, Whole Exome Sequencing (WES) utilizing next generation sequencing on an Illumina HiSeq 2000 platform was performed. Results revealed a novel homozygote mutation in ERCC8 gene (NM_000082: exon 11, c.1122G>C) in our patient. Another gene (ERCC6) which is also involved in Cockayne syndrome did not have any disease-causing mutations in the proband. The new identified mutation was then confirmed by Sanger sequencing in the proband, his parents and extended family members, confirming co-segregation with the disease. In addition, different bioinformatics programs which included Mutation Taster, I-Mutant v2.0, NNSplice, Combined Annotation Dependent Depletion (CADD), The PhastCons, Genomic Evolutationary Rate Profiling conservation score (GERP), and T-Coffee Multiple Sequence Alignment predicted the pathogenicity of the mutation. Our study identified a rare novel mutation in ERCC8 gene and help to provide accurate genetic counseling and prenatal diagnosis to minimize new affected individuals in this family.